Age at menopause is inversely related to the prevalence of common gynecologic cancers: a study based on NHANES - Cheng, Guangdong; Wang, Mengmeng; Sun, Hao; Lai, Jingjiang; Feng, Yukun; Liu, Hongjin; Shang, Yuwang; Zhao, Yuan; Zuo, Bingli; Lu, Youhua (Frontiers in Endocrinology, 2023)
The fluctuation or even loss of estrogen level caused by menopause in women, and most gynecological cancers often occur before and after menopause, so the age of menopause may be related to the occurrence of gynecological cancer.Aim: To investigate whether the age at menopause is independently associated with the incidence of gynecological cancers and to analyze the possible influencing factors.We selected the NHANES public database to conduct the study, and by excluding relevant influencing factors, we finally included 5706 NHANES participants who had full data on age at menopause and the occurrence of gynecologic cancers to analyze the relationship between the amount of age at menopause and gynecologic cancers based on univariate or multifactorial logistic regression analysis. Further, the relationship between age at menopause and the prevalence of different gynecologic cancers was investigated, and changes in the prevalence of different gynecologic cancers by age at menopause subgroups were observed. Finally, other relevant factors affecting the prevalence of gynecologic cancers were further investigated by subgroup analysis as well as subcluster analysis.Results: Univariate logistic regression analysis between age at menopause and gynecologic tumor prevalence revealed a negative association between age at menopause and the prevalence of common gynecologic cancers ovarian and cervical cancer, and after adjusting for the effects of covariates, a higher risk of gynecologic tumors was found with statistically significant differences at earlier age at menopause. The regression results showed a negative association between age at menopause and gynecologic cancer prevalence in cervical and ovarian cancer patients (P<0.01,P<0.01). Cervical cancer (OR: 0.91, 95% CI: 0.87,0.94) and ovarian cancer (OR: 0.90, 95% CI: 0.86, 0.95) were more prevalent among those with younger age at menopause.Age at menopause is negatively associated with the prevalence of cervical and ovarian cancers, and the earlier the age at menopause, the greater the risk of developing gynecological cancers.